2021
DOI: 10.7717/peerj.11122
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome and histological analyses provide insights into the skin pigmentation in Minxian black fur sheep (Ovis aries)

Abstract: Background Minxian black fur (MBF) sheep are found in the northwestern parts of China. These sheep have developed several special traits. Skin color is a phenotype subject to strong natural selection and diverse skin colors are likely a consequence of differences in gene regulation. Methods Skin structure, color differences, and gene expression (determined by RNA sequencing) were evaluated the Minxian black fur and Small-tail Han sheep (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
3
6
0
Order By: Relevance
“…KEGG analysis showed that DEGs were significantly enriched in tyrosine metabolism (4 DEGs), melanogenesis (4 DEGs), neuroactive ligand–receptor interaction (6 DEGs). The result is similar to the previous study [ 41 , 42 ]. Meanwhile, GO terms of m 6 A modified genes also involved in pigmentation, such as regulation of synaptic transmission, dopaminergic, melanosome assembly, regulation of dopamine metabolic process, melanosome organization, negative regulation of kinase activity and melanosome membrane, which is similar to GO enrichment of DEGs.…”
Section: Discussionsupporting
confidence: 92%
“…KEGG analysis showed that DEGs were significantly enriched in tyrosine metabolism (4 DEGs), melanogenesis (4 DEGs), neuroactive ligand–receptor interaction (6 DEGs). The result is similar to the previous study [ 41 , 42 ]. Meanwhile, GO terms of m 6 A modified genes also involved in pigmentation, such as regulation of synaptic transmission, dopaminergic, melanosome assembly, regulation of dopamine metabolic process, melanosome organization, negative regulation of kinase activity and melanosome membrane, which is similar to GO enrichment of DEGs.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of OCA2 can regulate eumelanin biosynthesis in several tissues. For example, OCA2 mRNA expression is higher in black Minxian black fur sheep than in white small-tail Han sheep ( Shi et al , 2021 ), which is consistent with our finding OCA2 mRNA exhibits higher expression in the skin tissue of Korean quail than in the skin of Beijing white quail. These phenomena primarily occur because the cells involved in pigmentation are the same in different tissues, and the pigment synthesis pathways and regulation mechanisms are similar in different breeds ( Lin et al , 2013 ).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, it was demonstrated that human skin pigmentation is complex, the genetic architecture varies by latitude and known pigmentation loci explain only a small fraction of the variance [ 36 ]. Likewise, similar outcomes have been reported in investigations in sheep and cattle [ 37 , 38 ]. Although some progress has been made in the elucidation of the genetic basis of skin pigmentation in humans [ 39 ], chickens [ 40 , 41 ], cattle [ 42 ], sheep [ 43 ] and so on, the genetics of skin colour are currently less understood than those of hair colour.…”
Section: Discussionsupporting
confidence: 89%